IMPLIKATUR PERCAKAPAN PADA HUMOR DEWASA (SHIMONETA) DALAM SERIAL ANIME â€œSEITOKAI YAKUINDOMOâ€ - Prabowo, Dimas Aditya; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to determine the forms of conversational implicatures andviolations of the maxim of cooperation in humorous dialogues contained in the SeitokaiYakuindomo anime series. The research data contained in this study are humorousdialogues posed by the characters in the Seitokai Yakuindomo anime series and theresearchers found that there are two forms of conversational implicatures used in theadult humor dialogues, namely conventional implicatures and special conversationalimplicatures and there are forms of violation of maxims. The cooperation in the humordialogue includes the violation of the maxim of relevance and the violation of the maximof qualityKey Words: Adult Jokes (Shimoneta), Implication of Conversation, CooperativePrinciple